Consideration of using virtual reality for teaching neonatal resuscitation to midwifery students. (July 2018) - Williams, Jessica; Jones, Donovan; Walker, Rohan
Abstract: Within the last decade, there has been significant change in the way tertiary midwifery education has been delivered to students. The use of blended teaching methods and the introduction of simulated learning experiences has been observed in the literature to improve students' self-confidence, competence, clinical judgement and decision-making abilities. Simulation is seen to be particularly important when practising skills that may be infrequently encountered in practice, such as clinical emergencies. Neonatal resuscitation is the most common neonatal emergency encountered within midwifery today, with up to 15% of babies requiring some form of resuscitation at birth. Recent research describes the benefits of using a multi-modal approach to teaching neonatal resuscitation, utilising both theory and simulated learning methods. One emerging method of simulation is that of virtual reality (VR), which has been recognised for its enormous educational potential in risk-free clinical skills training. Currently, however, there is limited research looking at the use of VR in emergency skills training. This article examines the literature to highlight the potential benefits that VR simulation could provide for emergency skills training, as well as the potential challenges that should be acknowledged. Highlights: Use of virtual reality is emerging within tertiary healthcare education and training. Virtual reality can further enhance the simulation experience for midwifery students. Neonatal resuscitation would be an ideal skill to teach using virtual reality. Consideration for potential benefits and challenges is required.